2017
DOI: 10.1007/s10143-017-0831-2
|View full text |Cite
|
Sign up to set email alerts
|

Routine placement of subdural drain after burr hole evacuation of chronic and subacute subdural hematoma: a contrarian evidence based approach

Abstract: The objective of this paper was to evaluate whether available evidence supporting placement of subdural drain placement after evacuation of chronic subdural haematoma (CSDH) is applicable to a cohort of patients managed by us. In this observational cohort study, clinical follow-up was obtained in 166 patients who underwent burr hole evacuation of CSDH without placement of subdural drain followed by 3 days of bed rest. The primary outcome studied was recurrence requiring reoperation. Factors predicting recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…All publications studied by us have concluded that the use of a closed drainage system gives significantly reduced rates of reaccumulation as opposed to not using drains after surgery. [11][12][13][14] Our operative philosophy is therefor based on the following points drawn from a study of literature (►Fig. 1):…”
Section: Discussionmentioning
confidence: 99%
“…All publications studied by us have concluded that the use of a closed drainage system gives significantly reduced rates of reaccumulation as opposed to not using drains after surgery. [11][12][13][14] Our operative philosophy is therefor based on the following points drawn from a study of literature (►Fig. 1):…”
Section: Discussionmentioning
confidence: 99%
“…We also recognize the great value and contribution of the randomized controlled trial (RCT) performed in 2009 by Santarius et al 4 , in which the use of a drain was effectively associated with a lower rate of recurrence of CSDH and lower rate of patient mortality 4 . The same author has a commendable list of publications in this regard, reinforcing the advantages of using a drain 5 .However, it is almost a decade since the publication of the RCT by Santarius et al, which was the sole RCT discussing this theme at the time, and more recently, some newer, respectable publications have brought to our attention the fact that the same results might not be achieved worldwide.In this regard, Gernsback et al 7 and Sivaraju et al 8 have recently reported, in two different respectable neurosurgical journals, that their results did not match with those found by Santarius et al 4 . In both cases, the use of a drain did not affect recurrence rates 7,8 .…”
mentioning
confidence: 80%
“…In this regard, Gernsback et al 7 and Sivaraju et al 8 have recently reported, in two different respectable neurosurgical journals, that their results did not match with those found by Santarius et al 4 . In both cases, the use of a drain did not affect recurrence rates 7,8 . We must highlight that neither of these recent studies were RCTs 7,8 .…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…CSDH often present weeks or months after the first bleed, as the initial hematoma liquefies, it expands. The increase of volume may result in increased in intracranial pressure and subsequent neurological complications [1][2][3]. CSDH is a profound cause of morbidity and mortality in elderly.…”
Section: Introductionmentioning
confidence: 99%